All-solid-state lithium battery, positive electrode, and preparation method
Patent Information
- Application Number
- CN202510873252.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2026-10-30
AI Technical Summary
但是,较低的电子电导率和明显的不可逆氧化还原反应导致高电压界面结构严重退化,使得富锂锰基正极材料在充放电过程动力学缓慢
[0028]本发明实施例中,正极的正极材料包括基体和包裹层;其中:基体为Li[LixNiaCobMncMy]O2;x+a+b+c+y=1,x>0,a>0,0<b<0.1,c>0,y>0,M为Al、Mg、Zn、Ti、Nb、Ta、W、Zr中的任意一种;包裹层为快离子导体利用掺杂和包覆协同作用,一方面通过在富锂锰基中引入高价态过渡金属元素形成梯度掺杂,掺杂效应增强了过渡金属-氧键,抑制了氧的释放和相变,稳定了层状结构,增强了电化学可逆性。通过快离子导体表面包覆,包覆层可以物理阻隔正极材料和电解液,防止材料表面高价金属阳离子和活性氧与电解液反应,也能抑制电解液中HF的侵蚀。快离子导体具有较高的离子导电率,在延缓界面反应的同时为材料表面提供了快速的锂离子通道,降低循环过程中材料的极化。
Smart Images

Figure CN123017871A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of batteries, and in particular to an all-solid-state lithium battery, a positive electrode of an all-solid-state lithium battery, and a method for preparing the positive electrode of an all-solid-state lithium battery. Background Technology
[0002] All-solid-state lithium batteries (ASSBs) have attracted much attention due to their safety, energy density, and cycle stability. Currently, the discharge specific capacity of the cathode limits the advancement of ASBs towards higher energy densities. Lithium-rich manganese-based cathode materials have become one of the most promising cathode materials for ASBs due to their discharge specific capacity ≥250 mAh / g, energy density ≥1000 Wh / kg, and low Co and Ni content. However, their low electronic conductivity and significant irreversible redox reactions lead to severe degradation of the high-voltage interface structure, resulting in slow charge-discharge kinetics.
[0003] Therefore, building and maintaining stable / fast Li+ and e- transport paths for all-solid-state batteries during long-term cycling remains a significant challenge. Summary of the Invention
[0004] In view of the above problems, a method for preparing an all-solid-state lithium battery, a cathode of an all-solid-state lithium battery, and a cathode of an all-solid-state lithium battery are proposed to overcome or at least partially solve the above problems. By introducing high-valence transition metal elements (e.g., Al, Mg, Zn, Ti, Nb, Ta, W, Zr) into a lithium-rich manganese base to form gradient doping, the doping effect enhances the transition metal-oxygen bond, suppresses oxygen release and phase transition, stabilizes the layered structure, and enhances electrochemical reversibility.
[0005] On the other hand, by coating the surface of the fast ion conductor, the coating layer can physically block the cathode material and the electrolyte, preventing the reaction of high-valence metal cations and active oxygen on the material surface with the electrolyte, and also inhibiting the corrosion of HF in the electrolyte. The fast ion conductor has high ionic conductivity, which, while delaying the interfacial reaction, provides a fast lithium-ion channel on the material surface, reduces the polarization of the material during cycling, increases the migration speed of lithium ions on the electrode surface, and thus improves the rate capability and cycle performance of the cathode material.
[0006] A positive electrode for an all-solid-state lithium battery, wherein the positive electrode material comprises a matrix and a coating layer; wherein:
[0007] The matrix is Li[Li x Ni a Co b Mn c M yO2; x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0, M is any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr;
[0008] The encapsulation layer is a fast ion conductor.
[0009] The present invention also provides an all-solid-state lithium battery, wherein the all-solid-state lithium battery includes a positive electrode as described above.
[0010] This invention also provides a method for preparing the positive electrode of an all-solid-state lithium battery, the method comprising:
[0011] A lithium-rich manganese-based precursor, a dopant containing M, and a lithium salt are mixed and then subjected to a first sintering to obtain a matrix; the matrix is Li[Li x Ni a Co b Mn c M y O2; x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0, M is any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr;
[0012] The matrix is mixed with the encapsulating agent and then sintered a second time to obtain the positive electrode material of the positive electrode; the encapsulating agent is a fast ion conductor;
[0013] The positive electrode is prepared based on the aforementioned positive electrode material.
[0014] Optionally, the encapsulating agent is Li7La3Zr2O 12 Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x Any of (PO4)3.
[0015] Optionally, the lithium-rich manganese-based precursor is Ni. a Co b Mn c (OH)2, a>0, 0<b<0.1, c>0.
[0016] Optionally, the mass ratio of M in the dopant to the mass of the lithium-rich manganese-based precursor is 1:(100-5000);
[0017] The mass ratio of the coating agent to the matrix is 1:(100-1000).
[0018] Optionally, the dopant is any one of aluminum source, magnesium source, zinc source, titanium source, niobium source, tantalum source, tungsten source, and zirconium source.
[0019] Optionally, the aluminum source is either aluminum nitrate or aluminum sulfate;
[0020] The magnesium source is either magnesium nitrate or magnesium acetate;
[0021] The zinc source is either zinc sulfate or zinc oxide;
[0022] The tantalum source is any one of tantalum oxalate, tantalum chloride, and tantalum sulfate.
[0023] The tungsten source is any one of tungsten chloride, ammonium tungstate, and sodium tungstate.
[0024] The zirconium source is either zirconium oxynitrate or zirconium oxide.
[0025] Optionally, the lithium salt is any one of lithium hydroxide, lithium carbonate, and lithium acetate.
[0026] Optionally, in the lithium-rich manganese-based precursor, the dopant containing M, and the lithium salt, the molar amount of Li / molar amount of TM = 1.4; wherein TM contains Ni, Co, Mn, and M; and the molar proportion of M in TM is 0.125 to 0.25.
[0027] The present invention has the following advantages:
[0028] In this embodiment of the invention, the positive electrode material includes a substrate and a coating layer; wherein: the substrate is Li[Li x Ni a Co b Mn c M y O2; x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0, M is any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr; the coating layer is a fast ion conductor utilizing the synergistic effect of doping and coating. On the one hand, by introducing high-valence transition metal elements into the lithium-rich manganese base to form gradient doping, the doping effect enhances the transition metal-oxygen bond, inhibits oxygen release and phase transition, stabilizes the layered structure, and enhances electrochemical reversibility. Through coating the surface of the fast ion conductor, the coating layer can physically block the cathode material and electrolyte, preventing high-valence metal cations and active oxygen on the material surface from reacting with the electrolyte, and also inhibiting the corrosion of HF in the electrolyte. The fast ion conductor has high ionic conductivity, providing a fast lithium-ion channel on the material surface while delaying interfacial reactions, reducing the polarization of the material during cycling. Attached Figure Description
[0029] To more clearly illustrate the technical solution of the present invention, the accompanying drawings used in the description of the present invention will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0030] Figure 1 This is a schematic diagram of a positive electrode material according to an embodiment of the present invention;
[0031] Figure 2 This is a flowchart illustrating the steps of a method for preparing the positive electrode of an all-solid-state lithium battery according to an embodiment of the present invention. Detailed Implementation
[0032] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0033] In one embodiment of the present invention, a positive electrode for an all-solid-state lithium battery is provided, such as... Figure 1 As shown, the positive electrode material includes a substrate 10 and a coating layer 11; wherein:
[0034] The matrix is Li[Li x Ni a Co b Mn c M y O2; x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0, M is any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr;
[0035] The coating layer is a fast ion conductor.
[0036] For example, M can be a high-valence transition metal element, such as any one of Al, Mg, Zn, Ti, Nb, Ta, W, and Zr; by introducing a high-valence transition metal element into a lithium-rich manganese-based matrix to form gradient doping, the doping effect enhances the transition metal-oxygen bond, suppresses oxygen release and phase transition, stabilizes the layered structure, and enhances electrochemical reversibility.
[0037] The coating layer can be a fast ion conductor, such as Li7La3Zr2O. 12 Li 3x La 2 / 3-x TiO3, Li 1+x Alx Ti 2-x One of (PO4)3. By coating the surface of a fast-ion conductor, the coating layer can physically block the cathode material and electrolyte, preventing the reaction of high-valence metal cations and active oxygen on the material surface with the electrolyte, and also inhibiting the corrosion of HF in the electrolyte. The fast-ion conductor has high ionic conductivity, providing a rapid lithium-ion channel on the material surface while delaying interfacial reactions, reducing material polarization during cycling, increasing the migration rate of lithium ions on the electrode surface, and thus improving the rate capability and cycle performance of the cathode material.
[0038] In another embodiment of the present invention, an all-solid-state lithium battery is provided, which may include the positive electrode of the all-solid-state lithium battery as mentioned in the above embodiments.
[0039] In another embodiment of the present invention, a method for preparing the positive electrode of an all-solid-state lithium battery is provided; such as Figure 2 The diagram shows a flowchart of the steps involved in preparing the positive electrode of an all-solid-state lithium battery according to an embodiment of the present invention.
[0040] like Figure 2 As shown, the method for preparing the positive electrode of this all-solid-state lithium battery may include the following steps:
[0041] Step 201: The lithium-rich manganese-based precursor, the dopant containing M, and the lithium salt are mixed and then sintered for the first time to obtain the matrix; the matrix is Li[Li x Ni a Co b Mn c M y O2; x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0, M is any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr.
[0042] In this embodiment of the invention, a lithium-rich manganese-based precursor, a dopant containing M, and a lithium salt are first mixed uniformly; then the mixture is sintered for the first time to obtain the matrix. The lithium-rich manganese-based precursor can be Ni. a Co b Mn c (OH)2, a>0, 0<b<0.1, c>0. M can be any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr.
[0043] The matrix obtained by sintering can be Li[Li x Ni a Co b Mn c M y]O2; among them, x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0.
[0044] In this embodiment of the invention, the synergistic effect of doping and coating is utilized. On the one hand, by introducing high-valence transition metal elements into lithium-rich manganese-based materials to form gradient doping, the doping effect enhances the transition metal-oxygen bond, suppresses oxygen release and phase transition, stabilizes the layered structure, and enhances electrochemical reversibility.
[0045] The first sintering temperature is 500-1000℃, the heating rate is 2-10℃ / min, the sintering atmosphere is pure oxygen, and the sintering holding time is 10-20h.
[0046] Step 202: Mix the matrix and the encapsulating agent and then perform a second sintering to obtain the positive electrode material; the encapsulating agent is a fast ion conductor.
[0047] After obtaining the matrix through sintering, the matrix and the encapsulating agent can be mixed uniformly, and then a second sintering is performed to obtain the positive electrode material as mentioned in the aforementioned embodiments; wherein, the encapsulating agent can be a fast ion conductor, and the encapsulating agent can be Li7La3Zr2O. 12 Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x Any of (PO4)3.
[0048] By coating the surface of a fast-ion conductor, the coating layer can physically block the cathode material and electrolyte, preventing the reaction of high-valence metal cations and active oxygen on the material surface with the electrolyte, and also inhibiting the corrosion of HF in the electrolyte. The fast-ion conductor has high ionic conductivity, providing a rapid lithium-ion channel on the material surface while delaying interfacial reactions. This reduces material polarization during cycling, increases the migration rate of lithium ions on the electrode surface, and thus improves the rate capability and cycle performance of the cathode material.
[0049] The second sintering temperature is 500-800℃, the heating rate is 2-10℃ / min, the sintering atmosphere is pure oxygen, and the sintering holding time is 4-12h.
[0050] Step 203: Prepare the positive electrode according to the positive electrode material.
[0051] After obtaining the cathode material, the cathode of an all-solid-state lithium battery can be prepared based on the cathode material.
[0052] In some feasible embodiments, the mass ratio of M in the dopant to the lithium-rich manganese-based precursor is 1:(100-5000); the mass ratio of the coating agent to the matrix is 1:(100-1000).
[0053] In some feasible embodiments, the dopant can be any one of aluminum source, magnesium source, zinc source, titanium source, niobium source, tantalum source, tungsten source, and zirconium source.
[0054] In some feasible embodiments, the aluminum source is either aluminum nitrate or aluminum sulfate;
[0055] The magnesium source can be either magnesium nitrate or magnesium acetate;
[0056] The zinc source can be either zinc sulfate or zinc oxide;
[0057] The tantalum source can be any one of tantalum oxalate, tantalum chloride, or tantalum sulfate.
[0058] The tungsten source can be any one of tungsten chloride, ammonium tungstate, or sodium tungstate.
[0059] The zirconium source can be either zirconium oxynitrate or zirconium oxide.
[0060] In some feasible embodiments, the lithium salt is any one of lithium hydroxide, lithium carbonate, and lithium acetate.
[0061] In some feasible embodiments, in the lithium-rich manganese-based precursor, the dopant containing M, and the lithium salt, the molar amount of Li / molar amount of TM = 1.4; wherein TM contains Ni, Co, Mn, and M; and the molar proportion of M in TM is 0.125 to 0.25.
[0062] The technical effects of the above-mentioned cathode material will be explained below through some experimental and control groups:
[0063] Experimental group 1:
[0064] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring a Li / TM (total transition metals Ni, Co, Mn, Ta) ratio of 1.4 (molar ratio) and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2;
[0065] The above-mentioned matrix and LLZO were ball-milled at 2500 rpm for 2 h, wherein the mass ratio of LLZO to matrix was 1:500; sintering was then performed, with the temperature increased to 600℃ at a heating rate of 3℃ / min and held for 8 h to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@LLZO.
[0066] Li 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@LLZO, conductive agent (SP, Super P), and binder (PVDF (Polyvinylidene Fluoride)) were uniformly mixed in a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto a current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC (Dimethyl Carbonate) / EC (Ethylene Carbonate) / DEC (Diethyl Carbonate) = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0067] Experimental group 2
[0068] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tungsten oxide, ensuring a Li / TM (total transition metals Ni, Co, Mn, W) ratio of 1.4 (molar ratio) and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.064 Co 0.064 Mn 0.512 W 0.16 O2;
[0069] The above-mentioned matrix and LLZO were ball-milled at 2500 rpm for 2 h, wherein the mass ratio of LLZO to matrix was 1:500; sintering was then performed, with the temperature increased to 600℃ at a heating rate of 3℃ / min and held for 8 h to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.064 Co 0.064 Mn 0.512 W 0.16 O2@LLZO.
[0070] Li 1.2 Ni 0.064 Co 0.064 Mn 0.512 W 0.16 O2@LLZO, conductive agent (SP, Super P), and binder (PVDF (Polyvinylidene Fluoride)) were uniformly mixed in a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto a current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC (Dimethyl Carbonate) / EC (Ethylene Carbonate) / DEC (Diethyl Carbonate) = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0071] Experimental group 3
[0072] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and zirconium oxide, ensuring a Li / TM (total transition metals Ni, Co, Mn, Zr) ratio of 1.4 (molar ratio) and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Zr 0.16 O2;
[0073] The above-mentioned matrix and LLZO were ball-milled at 2500 rpm for 2 h, wherein the mass ratio of LLZO to matrix was 1:500; sintering was then performed, with the temperature increased to 600℃ at a heating rate of 3℃ / min and held for 8 h to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Zr 0.16 O2@LLZO.
[0074] Li 1.2 Ni 0.064 Co 0.064 Mn 0.512 Zr 0.16 O2@LLZO, conductive agent (SP, Super P), and binder (PVDF (Polyvinylidene Fluoride)) were uniformly mixed in a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto a current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC (Dimethyl Carbonate) / EC (Ethylene Carbonate) / DEC (Diethyl Carbonate) = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0075] Experimental group 4
[0076] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring a Li / TM (total transition metals Ni, Co, Mn, Ta) ratio of 1.4 (molar ratio) and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2;
[0077] The above-mentioned matrix and LATP were ball-milled at 2500 rpm for 2 h, wherein the mass ratio of LATP to matrix was 1:500; sintering was then performed, with the temperature increased to 600℃ at a heating rate of 3℃ / min and held for 8 h to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@LATP.
[0078] Li 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@LATP, conductive agent (SP, Super P), and binder (PVDF (Polyvinylidene Fluoride)) were uniformly mixed in a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto the current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC (Dimethyl Carbonate) / EC (Ethylene Carbonate) / DEC (Diethyl Carbonate) = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0079] Experimental group 5
[0080] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring that the Li / TM (total amount of Ni, Co, Mn, Ta transition metals) ratio was 1.4 and the molar percentage of M in TM was 0.125. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.07 Co 0.07 Mn 0.56 Ta 0.1O2 .
[0081] The above-mentioned matrix and LLZO were ball-milled at 2500 rpm for 2 h, wherein the mass ratio of LLZO to matrix was 1:500. The mixture was then sintered, heated to 600 °C at a heating rate of 3 °C / min, and held at that temperature for 8 h to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.07 Co 0.07 Mn 0.56 Ta 0.1O2 @LLZO.
[0082] Li 1.2 Ni 0.07 Co 0.07 Mn 0.56 Ta 0.1O2 @LLZO, conductive agent (SP), and binder (PVDF) were uniformly mixed at a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto the current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut into strips, and the strips after rolling and stamping were used as the positive electrode, and the lithium metal sheet as the negative electrode. The electrolyte was DMC / EC / DEC = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0083] Experimental group 6
[0084] Weigh Ni 0.1 Co 0.1 Mn 0.8( OH)2 was mixed with lithium carbonate and tantalum oxide to ensure that the Li / TM (total amount of Ni, Co, Mn, Ta transition metals) ratio was 1.4, and the molar ratio of M in TM was 0.25. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.06 Co 0.06 Mn 0.48 Ta 0.2O2 The above matrix was ball-milled with LLZO at 2500 rpm for 2 hours, wherein the mass ratio of LLZO to lithium-rich manganese-based material was 1:500. The mixture was then sintered, heated to 600℃ at a rate of 3℃ / min, and held at that temperature for 8 hours to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.06 Co 0.06 Mn 0.48 Ta 0.2O2 @LLZO.
[0085] Li 1.2 Ni 0.06 Co 0.06 Mn 0.48 Ta 0.2O2 @LLZO, conductive agent (SP), and binder (PVDF) were uniformly mixed at a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto the current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut into strips, and the strips after rolling and stamping were used as the positive electrode, and the lithium metal sheet as the negative electrode. The electrolyte was DMC / EC / DEC = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0086] Experimental group 7
[0087] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring that the Li / TM (total amount of Ni, Co, Mn, Ta transition metals) ratio was 1.4 and the molar percentage of M in TM was 0.1. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.062 Co 0.062 Mn 0.496 Ta 0.08O2 .
[0088] The above matrix was ball-milled with LLZO at 2500 rpm for 2 hours, wherein the mass ratio of LLZO to lithium-rich manganese-based material was 1:500. The mixture was then sintered, heated to 600℃ at a rate of 3℃ / min, and held at that temperature for 8 hours to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.062 Co 0.062 Mn 0.496 Ta 0.08O2 @LLZO.
[0089] Li 1.2 Ni 0.062 Co 0.062 Mn 0.496 Ta 0.08O2@LLZO, conductive agent (SP), and binder (PVDF) were uniformly mixed at a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto the current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut into strips, and the strips after rolling and stamping were used as the positive electrode, and the lithium metal sheet as the negative electrode. The electrolyte was DMC / EC / DEC = 1 / 1 / 1 (1 mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0090] Experimental group 8
[0091] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring that the Li / TM (total amount of Ni, Co, Mn, Ta transition metals) ratio was 1.4 and the molar percentage of M in TM was 0.275. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.058 Co 0.058 Mn 0.464 Ta 0.22O2 .
[0092] The above matrix was ball-milled with LLZO at 2500 rpm for 2 hours, wherein the mass ratio of LLZO to lithium-rich manganese-based material was 1:500. The mixture was then sintered, heated to 600℃ at a rate of 3℃ / min, and held at that temperature for 8 hours to obtain the coated lithium-rich manganese-based material Li. 1.2 Ni 0.058 Co 0.058 Mn 0.464 Ta 0.22O2 @LLZO.
[0093] Li 1.2 Ni 0.058 Co 0.058 Mn 0.464 Ta 0.22O2@LLZO, conductive agent (SP), and binder (PVDF) were uniformly mixed at a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto the current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut into strips, and the strips after rolling and stamping were used as the positive electrode, and the lithium metal sheet as the negative electrode. The electrolyte was DMC / EC / DEC = 1 / 1 / 1 (1 mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0094] Comparison Group 1
[0095] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring a Li / TM (total transition metals of Ni, Co, Mn, and Ta) ratio of 1.4 and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, Ta-doped lithium-rich manganese-based material Li₂ was obtained. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2.
[0096] Li 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2, conductive agent (SP), and binder (PVDF) were uniformly mixed at a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto a current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC / EC / DEC = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0097] Comparison Group 2
[0098] Weigh Ni 0.1 Co 0.1 Mn 0.8(OH)₂ and lithium carbonate were mixed, ensuring a Li / TM (total Ni, Co, Mn) ratio of 1.4 and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000°C at a rate of 3°C / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li₁.₂Ni₀.₀₈Co₀.₀₈Mn₀.₆₄O₂, was obtained. This matrix was then ball-milled with LLZO at 2500 rpm for 2 hours, with an LLZO to lithium-rich manganese-based material mass ratio of 1:500. The mixture was then sintered, heated to 600°C at a rate of 3°C / min, and held for 8 hours to obtain the coated lithium-rich manganese-based material, Li₁.₂Ni₀.₀₈Co₀.₀₈Mn₀.₆₄O₂. 1.2 Ni 0.08 Co 0.08 Mn 0.64 O2@LLZO.
[0099] Li 1.2 Ni 0.08 Co 0.08 Mn 0.64 O2@LLZO, conductive agent (SP), and binder (PVDF) were uniformly mixed at a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a homogeneous slurry. The prepared slurry was then uniformly coated onto a current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC / EC / DEC = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0100] Comparison Group 3
[0101] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring a Li / TM (total transition metals Ni, Co, Mn, Ta) ratio of 1.4 (molar ratio) and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2;
[0102] The above-mentioned matrix and magnesium oxide were ball-milled at 2500 rpm for 2 hours, wherein the mass ratio of magnesium oxide to matrix was 1:500; sintering was then performed, with the temperature increased to 600℃ at a heating rate of 3℃ / min and held for 8 hours to obtain the coated lithium-rich manganese-based material Li. 1. 2Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@Mg2O3.
[0103] Li 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@Mg2O3, conductive agent (SP, Super P), and binder (PVDF (Polyvinylidene Fluoride)) were uniformly mixed in a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto a current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC (Dimethyl Carbonate) / EC (Ethylene Carbonate) / DEC (Diethyl Carbonate) = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0104] Comparison Group 4
[0105] Weigh Ni 0.1 Co 0.1 Mn 0.8 (OH)₂ was mixed with lithium carbonate and tantalum oxide, ensuring a Li / TM (total transition metals Ni, Co, Mn, Ta) ratio of 1.4 (molar ratio) and a M content of 2500 ppm. The mixture was then ball-milled at 2000 rpm for 2 hours. The homogeneous mixture was then sintered in a muffle furnace, heated to 1000℃ at a rate of 3℃ / min, and held for 12 hours. After natural cooling to room temperature, a Ta-doped lithium-rich manganese-based material matrix, Li, was obtained. 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2;
[0106] The above-mentioned matrix and alumina were ball-milled at 2500 rpm for 2 hours, wherein the mass ratio of alumina to matrix was 1:500; sintering was then performed, with the temperature increased to 600℃ at a heating rate of 3℃ / min and held for 8 hours to obtain the coated lithium-rich manganese-based material Li. 1. 2Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@Al2O3.
[0107] Li 1.2 Ni 0.064 Co 0.064 Mn 0.512 Ta 0.16 O2@Al2O3, conductive agent (SP, Super P), and binder (PVDF (Polyvinylidene Fluoride)) were uniformly mixed in a mass ratio of 8:1:1, and a certain amount of NMP solvent was added to prepare a uniform slurry. The prepared slurry was then uniformly coated onto a current collector, dried at 100℃, and then transferred to a 120℃ vacuum oven for further drying. The dried electrode sheets were cut, and the sheets after rolling and stamping were used as the positive electrode, while the lithium metal sheet was used as the negative electrode. The electrolyte was DMC (Dimethyl Carbonate) / EC (Ethylene Carbonate) / DEC (Diethyl Carbonate) = 1 / 1 / 1 (1mol / L LiPF6), and the cells were assembled into coin cells. The assembled coin cells were tested for rate performance and capacity at charge / discharge voltages ranging from 2.0V to 4.8V at 0.1C / 1C / 4C rates.
[0108] Table 1 compares the electrochemical and thermal performance of experimental groups 1-4 and control groups 1-4.
[0109] Table 1
[0110]
[0111] The table shows that the C initial discharge specific capacity and 1C 200-cycle capacity retention rate of experimental groups 1-8 are higher than those of control groups 1-4.
[0112] As shown in Table 1, the embodiments of the present invention introduce high-valence transition metal elements to form gradient doping. The doping effect enhances the transition metal-oxygen bond, suppresses oxygen release and phase transition, stabilizes the layered structure, and enhances electrochemical reversibility. Furthermore, the coating layer can physically block the cathode material and electrolyte, preventing the reaction of high-valence metal cations and active oxygen on the material surface with the electrolyte, and also inhibiting the corrosion of HF in the electrolyte. Additionally, the fast ion conductor has high ionic conductivity, providing a fast lithium-ion channel on the material surface while delaying interfacial reactions, reducing material polarization during cycling, increasing the migration speed of lithium ions on the electrode surface, and thus improving the rate capability and cycle performance of the cathode material.
[0113] Finally, it should be noted that in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, or article that includes said element.
[0114] The foregoing has provided a detailed description of an all-solid-state lithium battery, an all-solid-state lithium battery cathode, and a method for preparing an all-solid-state lithium battery cathode. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A positive electrode for an all-solid-state lithium battery, characterized in that, The positive electrode material comprises a matrix and a coating layer; wherein: The matrix is Li[Li x Ni a Co b Mn c M y O2; x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0, M is any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr; The encapsulation layer is a fast ion conductor.
2. A fully solid-state lithium battery, characterized in that, The all-solid-state lithium battery includes the positive electrode as described in claim 1.
3. A method for preparing the positive electrode of an all-solid-state lithium battery, characterized in that, The preparation method includes: A lithium-rich manganese-based precursor, a dopant containing M, and a lithium salt are mixed and then subjected to a first sintering to obtain a matrix; the matrix is Li[Li x Ni a Co b Mn c M y O2; x+a+b+c+y=1, x>0, a>0, 0<b<0.1, c>0, y>0, M is any one of Al, Mg, Zn, Ti, Nb, Ta, W, Zr; The matrix is mixed with the encapsulating agent and then sintered a second time to obtain the positive electrode material of the positive electrode; the encapsulating agent is a fast ion conductor; The positive electrode is prepared based on the aforementioned positive electrode material.
4. The preparation method according to claim 3, characterized in that, The encapsulating agent is Li7La3Zr2O 12 Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x Any of (PO4)3.
5. The preparation method according to any one of claims 3-4, characterized in that, The lithium-rich manganese-based precursor is Ni. a Co b Mn c (OH)2, a>0, 0<b<0.1, c>0.
6. The preparation method according to any one of claims 3-5, characterized in that, The mass ratio of M in the dopant to the mass of the lithium-rich manganese-based precursor is 1:(100-5000); The mass ratio of the coating agent to the matrix is 1:(100-1000).
7. The preparation method according to any one of claims 3-6, characterized in that, The dopant is any one of aluminum source, magnesium source, zinc source, titanium source, niobium source, tantalum source, tungsten source, and zirconium source.
8. The preparation method according to claim 7, characterized in that, The aluminum source is either aluminum nitrate or aluminum sulfate; The magnesium source is either magnesium nitrate or magnesium acetate; The zinc source is either zinc sulfate or zinc oxide; The tantalum source is any one of tantalum oxalate, tantalum chloride, and tantalum sulfate. The tungsten source is any one of tungsten chloride, ammonium tungstate, and sodium tungstate. The zirconium source is either zirconium oxynitrate or zirconium oxide.
9. The preparation method according to any one of claims 3-8, characterized in that, The lithium salt is any one of lithium hydroxide, lithium carbonate, and lithium acetate.
10. The preparation method according to any one of claims 3-9, characterized in that, In the lithium-rich manganese-based precursor, the dopant containing M, and the lithium salt, the molar amount of Li / molar amount of TM = 1.4; wherein TM contains Ni, Co, Mn, and M; the molar proportion of M in TM is 0.125 to 0.25.
